Carnitine acetyltransferase (CRAT) expression in macrophages is dispensable for nutrient stress sensing and inflammation - Goldberg, Emily L. (Mol Metab, 2017)
OBJECTIVE: Fatty acid oxidation in macrophages is thought to regulate inflammatory status and insulin-sensitivity. An important unanswered question in this field is whether carnitine acetyl-transferase (CrAT) that regulates fatty acid oxidation and mitochondrial acetyl-CoA balance is required to integrate nutrient stress sensing to inflammatory response in macrophages. METHODS: Mice with myeloid lineage-specific Crat deletion were subjected to several metabolic stressors, including high-fat diet-induced obesity, fasting, and LPS-induced endotoxemia. Their metabolic homeostasis was compared to that of Crat-sufficient littermate controls. Inflammatory potential of Crat-deficient and Crat-sufficient macrophages were measured both in vitro and in vivo. RESULTS: Our studies revealed that ablation of CrAT in myeloid lineage cells did not impact glucose homeostasis, insulin-action, adipose tissue leukocytosis, and inflammation when animals were confronted with a variety of metabolic stressors, including high-fat diet, fasting, or LPS-induced acute endotoxemia. CONCLUSIONS: These findings demonstrate that unlike muscle cells, substrate switch mechanisms that control macrophage energy metabolism and mitochondrial short-chain acyl-CoA pools during nutrient stress are controlled by pathways that are not solely reliant on CrAT.